Histomorphometric evaluation of a nano-sized eggshell-containing supplement as a natural alloplast: An animal study - Rania Salama; Mohammed Khashaba; Dalia El Rouby (Elsevier, 2019)
Background: Limitations of autogenous grafts have dictated the need for development of new biomaterials that can serve as allografts. A paradigm shift directed manufacturers to revert to nature in the search for such allografts. This study aimed to evaluate an eggshell-based supplement, Membrell's® BONEhealth Plus D3 & K2, indicated to support bone mineral density, as a natural bone graft material. Methods: Twelve 5 × 10 × 1 mm full-thickness cranial bone defects were created in six adult male New Zealand rabbits. Six defects were filled with Membrell's® BONEhealth™ Plus D3 & K2, and the others were left empty as control. The animals were sacrificed 14 days postoperatively. The defects were dissected and prepared for histological assessment. Bone formation was compared both qualitatively and quantitatively. The area percent of newly-formed bone was evaluated in five successive regions using image analysis. Statistical analysis was performed using unpaired t-test. Differences between the two groups were considered significant at p ≤ 0.05. Results: Cranial bone defects filled with the nano-sized eggshell powder "Membrell's® BONEhealth™ Plus D3 & K2" revealed significantly higher levels of osteoid, newly-formed, regularly-arranged bone trabeculae in the center of the defects (47.37% ± 1.12) compared to the control defects (21.6% ± 4.92), which revealed no bone formation. A rapid rate of resorption of the nano-sized eggshell powder and consequently a rapid osteogenic effect was evident. Conclusions: The eggshell-based graft powder, Membrell's® BONEhealth™ Plus D3 & K2, is a biocompatible material which has the potential to enhance new bone formation. Keywords: Eggshell, Allografts, Biocompatible materials, Osteogenesis